Asesmen Layak Fungsi Bangunan Gedung (Bangunan MSC Indosat Baturaden) - Miftachudin Chakiki (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The building to be utilized should undergo regular inspections and performance testing to determine whether it can function and operate according to its intended use. Compliance with administrative and technical regulations governing the utilization of buildings is demonstrated through the issuance of a Building Worthiness Certificate (SLF). This study aims to assess the compatibility of the building's function with the conditions during the planning phase and evaluate the structural feasibility of the building. It also seeks to implement the provisions of Government Regulation No. 16 of 2021 regarding the Implementation of Law No. 28 of 2002 on Buildings. Based on the research conducted, it can be concluded that the structural suitability of the MSC Indosat Baturaden building has changed compared to the planned building. Initially designed as a battery storage building, it is currently used as an MSC building or a facility for storing batteries and servers. Additionally, there are discrepancies in the area specified in the original Building Permit (IMB) compared to the current building. Further analysis of the building's structure and the application of current regulations regarding structural serviceability, including dynamic load analysis (earthquake), inter-story drift analysis, P-Delta analysis, and structural cross-section checks, concluded that the building is safe as it meets the requirements specified in SNI 1726:2019 and SNI 2847:2019. The highest structural cross-section capacity ratio was 0.2 < 1, and the inter-story drift value was 0.023 < 0.07. The existing concrete material meets the structural standards, with a characteristic compressive strength of 28.98 MPa. The results of the rebar scan detector test showed that the type of reinforcement used complies with the standards specified during the planning phase, referring to SNI 07–0408–1989. Overall, the structural analysis results for the MSC Indosat Baturaden building indicate that the building is safe and remains fit for use.